Infrastructure Facilities Academic staff Job Performance and Students Academic Performance in Tertiary Institutions in Nigeria - Simon Omoregie Ajayi (MultiTech Publisher, 2024)
This paper examined the impact of infrastructure facilities on academic staff job performance and students’ academic performance in tertiary institutions in Nigeria. This study is a review paper. Depending on secondary data that were collected from online and print publications. The paper ascertained that infrastructure facilities has significant relationship between infrastructure facilities and academic staff job performance and students’ academic performance in tertiary institutions. Based on this, the paper recommended increment in funding of tertiary institutions for the development of infrastructure facilities. Adequate financial support is essential to enable institutional managers to provide the necessary infrastructure facilities. Government should increase funding to ensure that tertiary institutions have access to adequate funds to address existing gaps and implement necessary upgrades to enhance the working environment for academic staff.